Synthesis, resolution, and applications of 3-amino-2,2-dimethy1-1,3-diphenylpropan-1-ol, a conformationally restricted 1,3-aminoalcohol - Patil, M. N.; Gonnade, Rajesh G.; Joshi, Navalkishore N. (Tetrahedron, 2010)
Efficient synthetic routes to both syn and anti diastereomers of a conformationally restricted 1,3-aminoalcohol were devised. Resolution of the aminoalcohols was accomplished through diastereomeric salt with R-(-)-O-acetyl mandelic acid. These aminoalcohols were examined as ligands for two standard reactions, namely, enantioselective addition of Et(2)Zn to aldehydes and reduction of prochiral ketones with BH(3). (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-Aminoalcohol; Aldol-Tishchenko reaction; Diethylzinc; Oxazaborinane; Resolution